Rancang Bangun Pembangkit Listrik Tenaga Surya Untuk Pemakaian Rumah Tangga Berbasis Internet Of Things - Pratama, Ilham; Susanto, Andri; Azis, Abdillah (Jurnal Teknik Elektro, 2024)
This study designs and tests a prototype of a Solar Power Plant (PLTS) for households based on the Internet of Things (IoT). This system converts solar energy into electrical energy stored in the battery and monitored by ESP32, the sensors will be displayed on the LCD and the Blynk platform. The test results show that the system takes 8.37 seconds to activate and 3.10 seconds to read the sensor. The solar panel voltage varies between 12.66V to 13.27V when the sun is hot, this indicates the effect of light intensity on voltage. The Blynk platform monitors and stores data on voltage, current, storage conditions, and light intensity in LUX units in real time, and provides graphs and gauges for further analysis. This study uses an efficient and environmentally friendly Offgrid PLTS system for household needs and needs when camping or other outdoor activities.